2021
DOI: 10.3390/agronomy11122445
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of Fir, Pine and Thyme Essential Oils and Their Effect on Onion (Allium cepa L.) Seed Quality

Abstract: Botrytis allii and B. cinerea are important seed-transmitted pathogens of onion. The aim of this study was to determine the chemical compositions of fir, pine and thyme essential oils and evaluate their effects on the germination, vigour and health of onion seeds. Gas Chromatography/Mass Spectroscopy was used for the analysis of the oils’ chemical compositions. Seed germination, vigour and health tests were performed on untreated seeds and on seeds treated with volatile compounds of the oils applied at a conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…on the onion seeds and frequently reduced their infestation with Botrytis spp. The lowest dose tested with antifungal activity and without phytotoxic effects was 0.2 µL cm −3 , while increasing the dose led to increased phytotoxicity [59].…”
Section: Activity Of Potential Basic Substances Against Fungi and Oom...mentioning
confidence: 93%
“…on the onion seeds and frequently reduced their infestation with Botrytis spp. The lowest dose tested with antifungal activity and without phytotoxic effects was 0.2 µL cm −3 , while increasing the dose led to increased phytotoxicity [59].…”
Section: Activity Of Potential Basic Substances Against Fungi and Oom...mentioning
confidence: 93%
“…These methods could significantly improve seed quality, reduce pathogen development and be harmless to the environment and human health. There have been reports on the use of essential oils for seed treatment, e.g., basil, fir, lemongrass, pine, sage and thyme on onion seed quality [7,8]. It has been shown that they can improve germination and seed vigour parameters and effectively inhibit pathogen development.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that they can improve germination and seed vigour parameters and effectively inhibit pathogen development. Dorna et al [7] reported that treating seeds with fir oil at the concentration of 0.2 µL cm −3 for 6 h effectively controlled Botrytis aliii, B. cinerea and Fusarium spp. and improved seed germination.…”
Section: Introductionmentioning
confidence: 99%